Penerapan Sistem Pendukung Keputusan Desa Terbaik untuk Pemasangan Jaringan Internet Menggunakan Metode MAUT - Novriansyah Putra (Bulletin of Information System Research, 2024)
The internet is currently a very important sector for everyday life, internet connection is not only needed in urban areas, but also in rural areas, especially for village government information systems, the cost of providing internet in rural areas is relatively high, however, the demand for creating an internet network is always high, this condition is utilized by internet service providers (ISP) internet service providers. SPK is a system that plays a role in the process of making a decision in a school, organization or company. Therefore, to determine the best village in installing a village internet network, the Multi Attribute utility method is needed. This MAUT method is a quantitative comparison method that usually combines measurements of different risk costs and benefits, each existing criterion has several alternatives that can provide solutions, to find alternatives that are close to the user's wishes, to identify them, multiplication is carried out on the predetermined priority scale, so that the best and closest results from these alternatives will be taken as a solution.